Urban Religious Expressions in the Digital Era: Representations of Piety in Islamic TikTok Content - Kiki Melisa; Amanda Agni Oktavia Ramadhani; Surawan Surawan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The rapid growth of social media, particularly TikTok, has created a new space for the dissemination of religious messages. This phenomenon raises questions about how piety is represented and reinterpreted in the digital sphere by urban youth. This study aims to analyze the forms of piety representation in Islamic preaching content on TikTok and to explore the reception of urban audiences toward such messages. A qualitative descriptive method was employed, using digital ethnography to observe five videos from three popular creators—@kadamsidik00, @amazmii, and @risyad_bay—along with audience responses in the comment sections. The findings reveal that Islamic preaching content on TikTok represents piety through three main dimensions: moral, ritual, and symbolic. Audience responses show diverse patterns, ranging from appreciative, critical, and reflective to humorous, reflecting the plurality of ways in which young urban audiences interpret religious messages. These findings emphasize that social media functions as a new discursive space where urban communities construct and negotiate their religious identities. Significantly, this study contributes to academic discourse by applying Stuart Hall’s theory of representation to the context of digital da’wah, while also offering practical insights for content creators, educators, and Islamic institutions in designing communication strategies that resonate with the dynamics of the digital generation.